Risk of infantile atopic dermatitis in neonatal lupus erythematosus: a retrospective cohort study - Sun, Wenqiang; Li, Yihui; Jin, Xinyun; Li, Huiwen; Sun, Zexi; Wang, Huawei; Liu, Xue; Li, Lili; Hu, Jinhui; Huo, Jie; Zhu, Xueping (Frontiers in Immunology, 2025)
ObjectivesThe onset and progression of atopic dermatitis (AD) are closely linked to autoimmune status. While AD has been observed in children with neonatal lupus erythematosus (NLE), its relationship with perinatal factors remains unclear. This study aimed to identify early-life risk factors for the development of AD in children with NLE within their first two years of life.MethodsWe conducted a multicenter, retrospective cohort study using electronic medical records and follow-up data from patients in the NLE cohort. Children were categorized into AD and non-AD groups based on whether they developed AD by age two. Univariate and multivariate analyses were performed to compare general and clinical data between the two groups.ResultsAD incidence in NLE patients was 27.27 (21/77). Compared to the non-AD group, the AD group had significantly lower use of oral probiotics and intravenous gamma globulin, but higher rates of small-for-gestational-age (SGA) status, hypocomplementemia, thrombocytopenia, anti-SSA, anti-SSB, double antibody (anti-SSA, anti-SSB) positivity, antibiotic use, and systemic glucocorticoid (GC) treatment. Logistic regression analysis revealed that oral probiotics were a protective factor against AD, while double antibody positivity and systemic GC were risk factors.ConclusionIn children with NLE, oral probiotics were associated with a reduced risk of AD, while double antibody positivity and systemic GC administration significantly increased the risk of AD within the first two years of life. However, the limited sample size in this study warrants further findings.